Agentivité sexuelle des femmes dans les films pornographiques critiques réalisés par des femmes - Julie Lavigne; Myriam Le Blanc Elie; Sabrina Maiorano (Glad!)
In the early days of the commercialization of hardcore pornography, heterosexual pornography portrays a generally unfaked sexuality in which women’s pleasure is subordinated. In reaction to this production, feminists have created a pornography that foregrounds the sexuality of cis women or trans people (lesbians, bisexuals, fluids, pansexuals, heterosexuals or queer). We have analyzed a corpus of 38 feminist pornographic films in order to identify sexual scripts. The analysis focuses on the question of women’s sexual agency, operationalized in three markers: the expression of consent, sexual preferences and the transformation of the traditional heterosexual script. The analysis of the selected films allowed us to confirm the presence of representations of women’s sexual agency.